Arba’atul Jawānib fī Ta’līmil Lugah wa Aṡāruhā Al Mutarattabah ‘Alā Takāmulil Mahārāt Al Lugawiyyah - nurlaila nurlaila (University of Darussalam Gontor, 2019)
AbstractThe principle of the four strands of language acquisition is to balance language learning that consist of those four strands equally. The first strand is an education through the inputs that are focused on meaning such as learning through listening and reading where the interest of the learner conveyed by language. The second, an education through the outputs focused on meaning such as learning speech and writing where the learner interested in transferring ideas to someone else perfectly. The third, education through full attention to language elements and features where the learner attracted to study of sounds, vocabularies, grammar and etc. The fourth, fluency development in the use of language elements and features in the four skills, listening, speaking, reading and writing. Basically, the ideal teaching for language learning has to be balanced in theses four aspects, each of them with twenty five percent of the time-teaching in the class. Three aspects focus on the meaning, thus three quarters of the quota for teaching is mostly focused on the meaning. The other aspect focuses on the elements and features of language. Through this balance, the goals of language learning will be achieved and from fluency in the use of elements of the language and the features of sounds, vocabularies and grammar, etc. So that the learner can communicate effectively and appropriately.Keywords: The four strands, Input, Output, Elements of language, Fluency, Balance. أربعة الجوانب فى تعليم اللغة و آثارها المترتبة على تكامل المهارات اللغويةنورليلىجامعة باتوسنكر الإسلامية الحكوميةnurlaila@iainbatusangkar.ac.idملخصالفكرة الرئيسية لأربعة الجوانب (four strands) هي إعطاء الحصة الواحدة لكل من أربعة الجوانب. أما الجانب الأول فهو التعليم من خلال المدخلات التي ترتكز على المعنى و هو التعليم من خلال الاستماع والقراءة حيث اهتم المتعلم التي نقلتها اللغة. و الجانب الثاني فهو التعليم من خلال المخرجات التي ترتكز على المعنى و هو التعليم من خلال الكلام والكتابة حيث اهتم المتعلم بنقل الأفكار إلى شخص آخر. و الجانب الثالث فهو التعليم من خلال الاهتمام الكامل بعناصر اللغة وملامحها و هو التعليم من خلال دراسة الأصوات و المفردات و النحو و غيرها. و الجانب الرابع فهو تنمية الطلاقة فى استخدام العناصر اللغوية وملامحها المدروسة فى المهارات الأربع من الاستماع والكلام والقراءة والكتابة. كان فى تعليم اللغة المثالي التوازن فى الجوانب الأربعة هذه فلكل جانب ٢٥ % من الحصة. تركّز ثلاثة الجوانب على المعنى و بالتالي ثلاثة أرباع من الحصة تركز في الغالب على المعنى. و الجانب الآخر يركّز على عناصر اللغة و ملامحها. من خلال هذا التوازن ستتحقّق الأهداف من تعليم اللغة من طلاقة فى استخدام عناصر اللغة و ملامحها من الأصوات والمفردات والنحو و غيرها بحيث يقدر المتعلم على الاتصال الفعال.الكلمات الرئيسية: أربعة الجوانب، المدخلات، المخرجات، عناصر اللغة، الطلاقة، التوازن